Optimizing Public EV Charging Station Locations in Denpasar-Bali Using the Set Covering Problem Method - Yuwono Wiarco; Ocky Soelistyo Pribadi; Ni Wayan Ryas Ganitri; Septiana Widi Astuti; Bobby Agung Hermawan (Politeknik Transportasi Darat Indonesia - STTD Bekasi, 2026)
The transition to electric vehicles (EVs) is an urgent measure to reduce urban emissions and support Indonesia’s sustainable energy agenda. However, the lack of adequate Public Electric Vehicle Charging Stations (SPKLU) remains a key barrier to EV adoption in Denpasar City. This study applies the Set Covering Problem (SCP) method to determine optimal SPKLU placement by analyzing transportation zones and EV ownership data. Findings show that EV ownership in Denpasar has increased on average by 198.7% annually over the past seven years, following an exponential trend ( , R² = 0.85), with projections estimating 396,445 EV units in five years. Based on coverage analysis, a minimum of ten SPKLU locations is needed to serve all sub-districts; five currently exist, and five additional sites are recommended in zones 27, 29, 32, 36, and 41 corresponding to Padangsambian, Ubung Kaja, Peguyangan Kangin, Pemogan, and Serangan. This research contributes a spatial optimization framework for policymakers to strategically expand EV infrastructure and ensure equitable access across urban zones.